Exploring How Event Catering Firms Can and/or Already Apply Supply Chain Management Concepts to be competitive - Kapadia, Ikhlaas (2013)
This paper provides an in-depth study about applying Supply Chain Management concepts to make event-catering firms competitive. SCM concepts have extended to various industries and this paper aims to extend the application of SCM concepts to the event-catering sector. To achieve this, relevant SCM concepts were analysed and compared with SCM initiatives in the event-catering sector. Firstly, SCM initiatives in the event catering sector were analysed using secondary data. Secondly, first hand data was collected via interviews with two event-catering firms; Fresh and Tasty. This provided a more in-depth understanding on the study. After the analyses of the findings, it was evident that there were few similarities and more differences in how both companies managed various functions of their supply chain. The analysis also revealed greater application of various SCM concepts by Fresh, in comparison to Tasty. Thirdly, upon thorough discussion of the findings, a gap was evident between how SCM concepts are applicable in theory and how they are practically applicable amongst both firms